2022
DOI: 10.3389/fmars.2021.733542
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass Meadows Reduce Wind-Wave Driven Sediment Resuspension in a Sheltered Environment

Abstract: Seagrass meadows are prominent in many coastal zones worldwide and significant contributors to global primary production. The large bottom roughness (or canopy) created by seagrass meadows substantially alters near-bed hydrodynamics and sediment transport. In this study, we investigate how a seagrass meadow in a low-energy environment (forced by local winds) modifies near-bed mean and wave-driven flows and assess how this relates to suspended sediment concentration (SSC). A two-week field study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…van Wesenbeeck et al, 2022 and consequently increases sedimentation e.g. D' Fagherazzi et al, 2012;Contti Neto et al, 2022. This mechanism is supposed to stabilise landscapes and to allow for vertical bed level accretion to keep up with sea level rise (Kirwan et al, 2016), suggesting that restoration of wetlands is an invariable nature-based solution for coastal protection (Schuerch et al, 2018). This contrasts with the main findings of this study.…”
Section: Multiscale Biomorphodynamic Interactions and Steady Statescontrasting
confidence: 86%
“…van Wesenbeeck et al, 2022 and consequently increases sedimentation e.g. D' Fagherazzi et al, 2012;Contti Neto et al, 2022. This mechanism is supposed to stabilise landscapes and to allow for vertical bed level accretion to keep up with sea level rise (Kirwan et al, 2016), suggesting that restoration of wetlands is an invariable nature-based solution for coastal protection (Schuerch et al, 2018). This contrasts with the main findings of this study.…”
Section: Multiscale Biomorphodynamic Interactions and Steady Statescontrasting
confidence: 86%
“…Previous works showed that vegetation dissipates hydrodynamic energy (e.g., van Wesenbeeck et al., 2022) and consequently increases sedimentation (e.g., Contti Neto et al., 2022; D’Alpaos et al., 2007; Fagherazzi et al., 2012; Nardin et al., 2018). This mechanism is supposed to stabilise landscapes and to allow for vertical bed level accretion to keep up with sea level rise (Kirwan et al., 2016), suggesting that restoration of wetlands is an invariable nature‐based solution for coastal protection (Schuerch et al., 2018).…”
Section: Discussionmentioning
confidence: 99%